Prekonsentrasi Dan Analisis Senyawa Renik Fenol Pada Sampel Perairan: Optimasi Kinerja Adsorben Pada Ekstraksi Padat-Cair - Armid, Armid (Universitas Halu Oleo, 2011)
Dissolved phenol in aquatic system has potential risk on human health.Accordingly, quantification of phenol compound presents in aquatic samples by improvedmethodis of significantly required in the field of Environmental Chemistry. This study aimsto evaluate the usefulness of Sep Pak C18 cartridge as the adsorbent of phenol compoundprior to analyzed by Gas Chromatography. Study is focused on the sample pH and flowrate optimization to gain the best performance of cartridge. Results indicated thatadjusting the pH of 1-2 and the flow rate of 5 ml/minute of sample was highlyrecommended. Such a method is relatively accurate within the range of concentration 1.2ppb 15 ppm of dissolved phenol, thus it may be considered as an alternative method toanalyze phenol which exists within trace level in the aquatic systems. The method has beensuccessfully applied to analyze phenol in seawater samples from Losari Beach, Makassar.